EVALUASI PENCEMARAN LOGAM BERAT Timbal (Pb) dan Cadmium (Cd) DI PERAIRAN TELUK BENOA, BALI - Annisa Ayu Permana; Deny Suhernawan Yusup (Program Studi Biologi Universitas Udayana, 2024)
The waters of Benoa Bay Bali are an area that has dense activity leading to generate pollution, particularly heavy metal pollutant. The objective of this research was to determine the heavy metal pollution, lead (Pb) and Cadmium (Cd) in sea water. The content of lead (Pb) and cadmium (Cd) in sea water was analysed by means of atomic absorption spectrophotometry (AAS). The results showed that the Pb content in seawater was not detected (ttd), while the Cadmium (Cd) content was detected from station II (0.5797 mg/L) and station III (0.3080 mg/L). The pollution index analysis show that the water quality status of Station I is classified as being in good condition, while stations II and III are classified as being in moderately polluted condition. Te STORET analysis shows that the waters of the Benoa Bay Bali area is classified as lightly polluted category (-8).